Homozygous Point Mutations in Platelet Glycoprotein ITGA2B Gene as Cause of Glanzmann Thrombasthenia in 2 Families - Sandrock, K.; Halimeh, S.; Wiegering, V.; Kappert, G.; Sauer, K.; Deeg, N.; Busse, E.; Zieger, B. (Klinische Pädiatrie, 2012)
Glanzmann thrombasthenia (GT) is a rare autosomal recessive bleeding disorder characterized by quantitative and/or qualitative defects of the platelet glycoprotein (GP) IIb/IIIa complex. Physiologically, the integrin GPIIb/IIIa binds Von Willebrand factor and fibrinogen on activated platelets. GT is caused by genetic alterations in ITGA2B or ITGB3 (genes encoding GPIIb and GPIIIa).This study describes 2 siblings diagnosed with GT type I associated with homozygous point mutations in ITGA2B. All patients presented with typical bleeding disorder including moderate hematomas, petechiae, and mucocutaneous bleedings.Both siblings showed severely reduced platelet aggregation especially after stimulation with collagen and adenosine diphosphate. Absence of platelet GPIIb/GPIIIa complex was determined using flow cytometry. Molecular genetic analysis revealed 2 distinct homozygous point mutations in exon 18 of ITGA2B. Family 1 was identified with c.1878G>C and family 2 with c.1787T>C substitution. While the c.1787T>C mutation causes a single amino acid substitution p.I565T, the c.1878G>C mutation (p.Q595H) is predicted to induce a mRNA splicing anomaly.These mutations were identified as cause of GT type I in the described patients. Patients with GT should be documented in a prospective register to verify the correlation between the severity of bleeding symptoms and the pathogenic mutation. This can have effects on therapeutic decisions.
Keywords: Glanzmann thrombasthenia; platelet function analyses; glycoprotein GPIIb/IIIa; point mutation